Prefab huizen - Álvarez, Ana Maria; Schleifer, Simone K. (Antwerp : BooQs, 2011)
The designs created a few years ago for non-specific, experimental prefabricated houses have made way for today's functional residences, which are more practical and respectful of the environment. This new volume displays the many uses and applications of this fascinating architectural specialty.
volwassenen
boek
Keywords: Prefab woningbouw -- vtr